Exciting science learning in elementary schools with the STREM model: innovative integration for students. - Pribadi, Pandu; Jamali, Arif; Nurahman, Arip; Jufriansah, Adi; Kartika , Ika (Insitut Pendidikan Indonesia, 2024)
Science learning in elementary schools often faces challenges in student engagement and conventional teaching methods. The STREM model offers an interdisciplinary approach that not only improves science understanding but also integrates Islamic values. Therefore, this study aims to analyse the effectiveness of applying the STREM model in improving students' understanding and engagement in science learning at one private elementary school in the West Java province. This study used the Kemmis and McTaggart CAR model with 2-3 cycles, consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, learning outcome tests (pre-test and post-test), and student response questionnaires, then analysed descriptively quantitatively and qualitatively. The results showed that the application of the STREM model improved student learning outcomes, with the average score increasing from 68 to 87, and a decrease in students in the